Regenerative Protocol for Knee Degeneration: A Case Study with Five-Year Follow-Up - Russ, Kenneth; Yoo, Philip; Lambert, Naomi; Lee, Alexis; Shou, John; Barrett, Tyler (Archives of Clinical and Biomedical Research, 2025)
Background/Objectives: Knee osteoarthritis (OA) is a progressive and disabling musculoskeletal disorder characterized by the degeneration of joint cartilage, leading to reduced range of motion and diminished quality of life. Globally, knee OA is estimated to account for approximately 80% of all osteoarthritis cases. The current standard of care is to provide conservative treatment with medication and lifestyle changes, but when they fail, surgical intervention may be required. Approximately 69% of patients with knee OA undergo total knee replacement surgery. Methods: The patient in this case study is an 85-year-old female who failed standard conservative care, presenting with advanced knee OA, poor posture, and an antalgic gait. The patient opted for regenerative medicine-focused care prior to seeking surgical intervention. The protocol included several regenerative therapies, pulsed electromagnetic field therapy (PEMF), myofascial release therapy, red lightemitting diode treatment (red light therapy), and a connective tissue transplant with a Wharton’s jelly tissue allograft. Results: Prior to treatment, the patient reported extreme pain. At the 3-month follow-up, she noted substantial pain reduction, and by the 12-month mark, reported complete resolution of pain. At a 5-year follow-up, the patient continued to report the absence of knee pain. Conclusions: This study observes the sustained improvement in pain and functional outcomes following a multimodal care approach. Aligning complementary regenerative protocols to target root causes instead of focusing on symptom management could improve outcomes-based care practices and should be further studied.